Age-Specific Prevalence and Factors Associated With Normal Blood Pressure Among US Adults. (2nd October 2021) - Muntner, Paul; Jaeger, Byron C; Hardy, Shakia T; Foti, Kathryn; Reynolds, Kristi; Whelton, Paul K; Bowling, C Barrett
Abstract: Background: The mean systolic blood pressure (SBP) for US adults increases with age. Determining characteristics of US adults ≥65 years with normal blood pressure (BP) may inform approaches to prevent this increase. Methods: We analyzed US National Health and Nutrition Examination Survey 2011–2018 data ( n = 21, 581). BP was measured up to 3 times and averaged. Normal BP was defined as SBP <120 mm Hg and diastolic BP (DBP) <80 mm Hg among participants not taking antihypertensive medication. Those with SBP ≥120 mm Hg, DBP ≥80 mm Hg, self-reporting having hypertension or taking antihypertensive medication were categorized as having elevated BP or hypertension. Results: The prevalence of normal BP was 57.8%, 25.3%, 11.2%, and 5.0% among US adults who were 18–44, 45–64, 65–74, and ≥75 years, respectively. After multivariable adjustment, in US adults ≥65 years of age, normal BP vs. elevated BP/hypertension was more common among those with moderate and no vs. heavy alcohol consumption (prevalence ratio [PR] 3.03; 95% confidence interval [CI] 1.25–7.36 and 2.53; 95% CI 0.96–6.65, respectively), ≥150 vs. <150 minutes of physical activity per week (PR = 1.44; 95% CI 1.01–2.05), overweight and normal weight vs. obesity (PR = 1.88; 95% CI 1.22–2.90 and 2.94; 95% CI 1.89–4.59, respectively), and a high Dietary Approaches to Stop Hypertension score (PR = 1.43; 95% CI 1.00–2.05). US adults ≥65 years with normal BP vs. elevated BP/hypertension were less likely to have good or fair/poor vs. excellent/very good self-rated health, diabetes, albuminuria, atherosclerotic cardiovascular disease, and heart failure. Conclusions: Among US adults ≥65 years, normal BP was associated with healthy lifestyle factors and a lower prevalence of adverse health conditions.